Analytic Solution for the RL Electric Circuit Model in Fractional Order - P. V. Shah; A. D. Patel; I. A. Salehbhai; A. K. Shukla (Abstract and Applied Analysis)
This paper provides an analytic solution of RL electrical circuit described by a fractional differential equation of the order 0<α≤1. We use the Laplace transform of the fractional derivative in the Caputo sense. Some special cases for the different source terms have also been discussed.